Snow White and the seven dwarfs [videorecording (Blu-Ray + DVD)] - Churchill, Frank, 1901-1942; Harline, Leigh; Smith, Paul J. (Paul Joseph), 1906-1985; Grimm, Jacob, 1785-1863; Grimm, Wilhelm, 1786-1859 (Disney Blu-ray., 2009)
Join the beautiful princess Snow White as she escapes her jealous stepmother, the queen, and befriends a lovable group of dwarfs. But when she falls under the queen's wicked spell, only true love's kiss can save her.